SELF-COMPASSION AND PSYCHOLOGICAL WELL-BEING AMONG EMPLOYEES IN COMPANIES IMPLEMENTING LAYOFFS - Presantoro, Elisye Canaya Prameswariputri; Kembaren, Esther Muliana (Atma Jaya Catholic University of Indonesia, 2023)
The COVID-19 pandemic has led to mass layoffs in companies worldwide, including Indonesia, which has been further exacerbated by the global recession in 2023. These mass layoffs not only impact the mental well-being of affected employees but also the psychological state of those still employed in related companies. Previous studies have shown that the uncertain employment situation creates feelings of worry, demotivation, difficulty sleeping, and unexplained anger. This study focuses on the importance of self-compassion, which encourages individuals to accept their imperfections and negative emotions without drowning in them. The research using Spearman’s correlation, conducted in Jakarta with a sample size of 101 active employees whose companies have recently carried out mass layoffs, found a significant positive relationship between self-compassion and psychological well-being of employees in companies that have terminated employment (r = 0.821, p < 0.05). The study suggests that self-compassion can be an adaptive strategy to promote well-being and positive psychological functioning during difficult times. Further research could explore different data collection techniques and study subjects.